Pengaruh Kepercayaan Konsumen, Promosi Media Sosial dan Celebrity Endoser Terhadap Minat Beli Konsumen Pada Online Shop Shopee - Hilyatun Nisak; Sukaris Sukaris (Universitas Muhammadiyah Gresik, 2022)
Background - Development of technology and information on the economic aspect has changed the media for selling businesses in developing their business. Objective - This study aims to examine the effect of consumer trust, social media-based promotions, and celebrity endorsers on consumer buying interest in online shop shopee. Design/Methodology/Approach - This study using quantitative methods. This research was conducted at the Muhammadiyah University of Gresik. The number of respondents used was 85 students. Data collection was carried out by distributing questionnaires. The analysis technique used in this study is multiple linear regression analysis. The results of the questionnaire in the study were tested using the SPSS version 24 program. Findings - The analysis show that the variables of consumer trust, social media-based promotions, and celebrity endorsers have a positive and significant effect on consumer buying interest in online shop shopee. Research implications - Influence The highest score is obtained from the results of multiple linear regression coefficient analysis on the social media promotion variable of 0.419, which means that the higher the social media promotion is carried out, the higher the purchase intention that arises from consumers. Research limitations - this research was limited to users of the shopee platform for active management students in 2018 Muhammadiyah University of Gresik.